Proceedings of the international conference dedicated to the memory of Academician Ubaydulla Karimov : new perspectives for the study of Islamic culture, history and art in Uzbekistan May 2021, Tashkent (İstanbul)
758 sayfa
Keywords: “This book contains the proceedings of the international conference on “New Perspectives for the Study of Islamic Culture, History and Art in Uzbekistan” dedicated to the memory of Academician Ubaydulla Karimov which was organized by IRCICA and Al-Biruni Institute of Oriental Studies of the Academy of Sciences of the Republic of Uzbekistan (Tashkent) online and offline, on 28 May 2021. The book, under print as the present Newsletter goes to press, includes a total of 84 articles in the Uzbek, Russian and Turkish languages, each accompanied by its abstract in English. Academician Ubaydulla Karimov (1920-1997), to whom the conference was dedicated, is introduced at the beginning of the book by Surayyo Ubaydullaevna Karimova with a comprehensive article. Both a chemist and an orientalist, through his research work Karimov presented scholarly evidence to some important aspects of the contributions of Central Asia to world science and civilization. The first chapter, on “History and Source Studies” contains forty articles addressing a variety of themes, from science and medicine to economy and waqfs, from influential persons and institutions to international relations, from the discovery of previously unknown works to emerging topics and new methods in Islamic studies. The twenty-nine articles presented in the second chapter are devoted to “Islamic Studies”. They result from recent research on specialized topics in the history of Quranic sciences, philosophy, natural sciences, architecture and archeology, and the heritage of medieval scientists and scholars. The third chapter contains fifteen articles in “Philology” contributed by specialists and researchers interested in the linguistic and literary processes in Central Asia. Considering their number and remarkable diversity, this collection of articles constitutes a representative sample of current academic research activity in Uzbekistan in the fields of the humanities and social sciences relating to the history and culture of the Islamic world“ --